2014
DOI: 10.4314/ahs.v13i4.14
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HBV and HIV co-infection in children and outcomes following highly active antiretroviral therapy (HAART) in Uyo, South-South Nigeria

Abstract: Background: Human Immunodeficiency Virus/ Hepatitis B Virus (HIV/HBV) co-infection in Nigerian children has emerged as a major concern with the advent of HAART. Its impact on the immune system and liver has not been extensively studied in children. Objectives: To determine the prevalence of HBV seropositivity among HIV positive children on HAART and its effect on immune response and liver enzymes. Methods: All consecutive HIV positive children aged two months to seventeen years on HAART constituted the study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
17
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
4
17
1
Order By: Relevance
“…Dual or triple infections with HBV or HCV upsurges the menace for hepatotoxicity of HAART and possibility of inception of an AIDS-defining illness, likened with infection with HIV only 8,34,35,39 . Studies previously have proposed that dual positivity of HIV/HBV or HIV/HCV and triple positivity HIV/HBV/HCV have dampened immune reaction to HAART likened with those with only HIV [40][41][42] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Dual or triple infections with HBV or HCV upsurges the menace for hepatotoxicity of HAART and possibility of inception of an AIDS-defining illness, likened with infection with HIV only 8,34,35,39 . Studies previously have proposed that dual positivity of HIV/HBV or HIV/HCV and triple positivity HIV/HBV/HCV have dampened immune reaction to HAART likened with those with only HIV [40][41][42] .…”
mentioning
confidence: 99%
“…Highly active antiretroviral therapy (HAART) has distorted HIV and AIDS from a consistently deadly ailment into a controllable long-lasting infection and has been presented to reinstate CD4+ cells in HIV positive persons 8,33,34 . The achievements of HAART might be conceded by dual or triple infections with hepatitis viruses as they are recognized to have antagonistic consequences on the scenario of HIV and hepatitis infections 8,34,35 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data from Nigeria, an endemic country for both viruses, show a seroprevalence rate of 6% among HBV/HIV coinfected children. In an extensive review of HBV/HIV coinfected children, one African study showed that in the long term, anti-HBe seroconversion did not result in virological control, contrary to patients with HBV monoinfection, and, as expected, that those with lower CD4+T-lymphocyte counts were unable to sustain a virological response for HBV and showed higher VHB DNA levels (67)(68)(69)(70)(71).…”
mentioning
confidence: 69%
“…Studies have revealed that Africa, especially the Western and Southern regions, have the highest prevalence rate of HIV/HBV co-infection in the world [3] [31]. The HIV/HBV co-infection rate in Africa is attributed to the 60 million prevalence rate of hepatitis B [9] [32]. A study conducted among 115 HIV infected pregnant women in Borkina Faso by Ilboudo, et al [33] shows a 12.17% prevalence rate.…”
Section: R E T R a C T E Dmentioning
confidence: 99%